Deteksi Antibodi dan Antigen Cacing Filaria dan Indeks Entomologi Vektor Potensial Filariasis di Kota Langsa Provinsi Aceh - Yulidar Yulidar; Veny Wilya; Rosdiana Rosdiana; Yasir Yasir (Biotik, 2019)
Humans can be infected with filariasis through mosquito bites with filaria worms in infective larva stage (L3). This study was conducted to detect the antibody, antigen, and the entomology index of potential mosquito vectors of filariasis in Langsa City. This research was conducted in Matang Seulimeng Village and Sungai Paoh Firdaus in Langsa City on November 2016 with 600 respondents. To determine the level of exposure to the infection source, a finger blood survey was conducted with a quick check using the rapid diagnostic test (RDT). RDT used is Brugia test to measure antibodies and ICT (Immuno Chromatographic Test) to measure filaria worm antigens. The existence of potential vectors is measured by entomology index, which are mosquito density, relative abundance, frequency of mosquitoes caught and species dominance. As the result, there were no respondent have been found positive for antibodies or filarial worms antigens in their blood. For the vector data, the potential mosquito vector of filariasis in Langsa City is Culex quinquifasciatus (23%) with peak biting activity at 01.00 02.00 pm.